ANALYSIS OF THE EFFECT OF IMPLEMENTING A DIGITAL TECHNOLOGY-BASED ACCOUNTING SYSTEM ON THE FINANCIAL PERFORMANCE OF MSME’S IN INDONESIA - Fitri Komariyah (Transpublika Publisher, 2024)
The primary objective of this study is to examine the impact of introducing a digital technology-driven accounting system on the financial outcomes of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In today's digital age, integrating technology into accounting systems plays a crucial role in enhancing the efficiency and transparency of financial reporting in MSMEs. The research employs a quantitative approach, utilizing a survey method to gather data from 150 MSMEs operating across various industries. Through the analysis of data using multiple linear regression, the study aims to assess the correlation between the implementation of a digital accounting system and financial performance, as measured by metrics such as profitability, cost effectiveness, and liquidity. The findings of this study reveal a positive and significant impact of incorporating a digital technology-based accounting system on the financial performance of MSMEs. The results suggest that MSMEs that embrace accounting technology demonstrate superior financial performance in comparison to those that adhere to traditional approaches. Consequently, this research imparts practical implications for MSME operators, encouraging them to actively adopt digital technology as a means to enhance financial performance and gain a competitive edge in the market.